Relationship of cysteine‐rich secretory protein‐3 gene and protein with semen quality in stallions. Issue 1 (19th September 2018) - Restrepo, Giovanni; Rojano, Benjamín; Usuga, Alexandra
Contents: Cysteine‐rich secretory protein‐3 (CRISP‐3) and some of its nonsynonymous polymorphism have been related to the fertility and freezability of stallion semen; however, the role of the CRISP‐3 gene and its seminal plasma protein in the raw semen quality is still unknown. The aim of this study was to evaluate the relationship of CRISP‐3 with semen quality in stallions. DNA was obtained from blood samples of 100 stallions, from which 30 stallions were randomly selected to obtain 60 ejaculates. Through PCR amplification and sequencing, the variation of four nonsynonymous SNPs from CRISP‐3 was identified and haplotypes were derived. Semen quality was assessed through the total motility (MOT), sperm vitality (SV), normal morphology (NM), functional integrity of membrane (MI) and a seminal quality index (SQi). CRISP‐3 protein content of seminal plasma (SP) was determined by ELISA. The effect of the genotype, the haplotype and the concentration of the CRISP‐3 protein on the seminal quality were evaluated through generalized linear models and linear regression analyses. Homozygous genotypes for SNP1, SNP2 and SNP3 and the heterozygous genotype for SNP4 showed a positive effect on seminal quality. Different haplotypes with positive effect on MOT, SV, NM, MI and SQi were identified. The allelic substitution analysis resulted in positive regression coefficients for MOT (SNP2) and MI (SNP2 and SNP3). A high level of CRISP‐3 resulted in a higher MOT and SQi. It is concluded that the quality of stallion semen is influenced by the genotype of CRISP‐3 and the concentration of CRISP‐3 protein in SP.